NEW ASPECTS OF DIAGNOSTICS OF MYOCARDIAL INFARCTION - Yakubova D. M.; Nabiyeva F. S.; Murtazayeva N.B. (Web of Journals Publishing, 2025)
Myocardial infarction often referred to as a heart attack, is an acute condition that results from a blockage in a coronary artery. This causes damage to the heart muscle due to lack of oxygen. The causes of myocardial infarction are varied, but the most common risk factors are smoking, high blood pressure, high cholesterol, and diabetes.
Keywords: Myocardial infarction, diagnostics, troponin I and T, myoglobin, creatine kinase, aspartate aminotransferase, lactate dehydrogenase, natriuretic peptide, electrocardiography.